IMPLEMENTASI PBL BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS KELAS XI SMA - N. L. P Sumasari; Sukadi Sukadi; I. P. Sriartha (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
This study investigates deficiencies in critical thinking skills among Grade XI students at SMA Negeri 2 Mengwi. The research aims to: (1) assess the effectiveness of the Problem-Based Learning model supplemented with Mind Mapping in enhancing students' critical thinking abilities; (2) examine the impact of the Problem-Based Learning model combined with Mind Mapping techniques; and (3) evaluate the effectiveness of the Problem-Based Learning model integrated with Mind Mapping in improving students' critical thinking skills. The study employs a quasi-experimental method with a quantitative approach. Data were analyzed using descriptive and inferential statistical techniques. This research constitutes a quantitative correlational analysis involving two sample groups—an experimental class and a control class—comprising 72 Grade XI students. Observation sheets and the analysis of learning outcome data were used to compile data on critical thinking. The dependent variable in this study is critical thinking ability. The research utilizes the Problem-Based Learning (PBL) paradigm, with Mind Mapping serving as the independent variable. Research hypotheses were evaluated using statistical tests (hypothesis testing). The following conclusions were drawn from the study: Mind Mapping enhances the implementation of the Problem-Based Learning (PBL) paradigm and significantly influences social learning instruction. The F-statistic was 99.412, with a p-value of less than 0.05. Observations indicated an improvement in critical thinking abilities. The implementation of the Problem-Based Learning (PBL) paradigm significantly improved critical thinking skills. The significance value was 0.514, indicating data homogeneity (as the value exceeded 0.05). The mean critical thinking score in the experimental class rose from 77.528 in the pretest to 82.306 in the posttest, whereas in the control class, it increased from 77.694 in the pretest to 78.694 in the posttest. Hypothesis test results demonstrate that the improvement in the experimental class was significantly greater than that in the control class (p < 0.05).